If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + -8m = 14 + -5m Solving 5 + -8m = 14 + -5m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '5m' to each side of the equation. 5 + -8m + 5m = 14 + -5m + 5m Combine like terms: -8m + 5m = -3m 5 + -3m = 14 + -5m + 5m Combine like terms: -5m + 5m = 0 5 + -3m = 14 + 0 5 + -3m = 14 Add '-5' to each side of the equation. 5 + -5 + -3m = 14 + -5 Combine like terms: 5 + -5 = 0 0 + -3m = 14 + -5 -3m = 14 + -5 Combine like terms: 14 + -5 = 9 -3m = 9 Divide each side by '-3'. m = -3 Simplifying m = -3
| 1.7-x=1.2 | | g/-4=-4.21 | | x+6x*-9=30 | | 5x^4-40x^2=0 | | M+23=94 | | 5k+4=3k-2k | | 3.1=x-1.5 | | 4/6r=5 | | x+6a*-9=30 | | 3n-n=4+n | | x=10*log(100) | | x-0.6=1.1 | | g-4= -4.21 | | 4z+5=6z-3z | | r/2=-18 | | -28=-2(w+7) | | x=1000*log | | -12+8n=-2n+4n | | u=2u-64 | | 12n+20=(n+5)*7 | | -4k=-19.6 | | c=40+55h | | 14x-5=12x-5 | | (n-5)*6=3n-6 | | 2.6+10m=8.29 | | -2(x+2)=4-(5x-7) | | 4x+6=2+3x-1 | | (n-2)*3=4n-10 | | -5x-49=113 | | 3t-14=2t+10 | | 6.1=-9+x | | 8x*4+4=68 |